2021
DOI: 10.1177/0081246321994452
|View full text |Cite
|
Sign up to set email alerts
|

Depression among health care students in the time of COVID-19: the mediating role of resilience in the hopelessness–depression relationship

Abstract: COVID-19 spread rapidly across the world, and by March 2020, the first case of COVID-19 was identified in South Africa. Lockdown-related measures such as restricted movement and isolation were implemented to contain the virus. Combined with these measures, factors such as economic decline, job losses, and food shortages can cause numerous mental health sequelae such as depression. Feelings of hopelessness and helplessness as well as cases of suicide have been reported around the world due to the pandemic and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
(43 reference statements)
4
15
0
Order By: Relevance
“…Symptoms of depression, anxiety, and stress that represent the negative dimension significantly increased between spring 2020 and spring 2021 (confirmation of Hypothesis 1a). This finding is in line with previous research (e.g., Bueno-Notivol et al 2020 ; Pretorius 2021 ). The fight against Covid-19 resulted in significant and emotionally challenging changes in different areas of people’s lives, for example, social isolation, job loss, and permanent worry about one’s health and the health of close others, which could contribute to the increase of the negative symptoms (Klomek 2020 ; Bayın et al 2021 ; Evans et al 2021 ).…”
Section: Discussionsupporting
confidence: 94%
“…Symptoms of depression, anxiety, and stress that represent the negative dimension significantly increased between spring 2020 and spring 2021 (confirmation of Hypothesis 1a). This finding is in line with previous research (e.g., Bueno-Notivol et al 2020 ; Pretorius 2021 ). The fight against Covid-19 resulted in significant and emotionally challenging changes in different areas of people’s lives, for example, social isolation, job loss, and permanent worry about one’s health and the health of close others, which could contribute to the increase of the negative symptoms (Klomek 2020 ; Bayın et al 2021 ; Evans et al 2021 ).…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, the mean score of hopelessness was 6.20 (0-20), with a standard deviation of 4.98. These figures are higher than similar figures in studies conducted in South Africa or the study of Kocalevent et al (2017) [32,33]. In the present study, approximately one-third of students reported a minimum level of hopelessness, and 6% reported a high level of hopelessness, which is consistent with the findings of a study by El-Zoghby et al [34], who reported that more than half of Egyptian adults had severe mental health problems.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, a descriptive study by Kizilkurt et al in Turkey supports the findings of our study [36]. In their study, marital status was directly related to hopelessness and anxiety symptoms, as most married people were concerned about food shortages, laundry and disinfection, and even the delay in their children's education due to home quarantine [32]. In addition to all the information about the impact of social support on hopelessness, Labrague et al, in their study, showed a statistically significant and inverse relationship between social support, aggression and hopelessness among nurses, so that social support was able to reduce the harmful and stressful effects of the environment [40].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, the results of the present study also suggest that satisfaction with distance learning affects psychological resilience, and both, together, can reduce symptoms of depression and anxiety. The impact of psychological resilience on depression, anxiety, and stress during the COVID-19 pandemic has already been confirmed by research in China within the general population [ 41 ], among healthcare professionals [ 42 ], and among health science students [ 43 ]. Research also confirms the need for increased support for the student population, as identified in a study [ 44 ].…”
Section: Discussionmentioning
confidence: 94%